Tailoring Nanosensor Devices for Ion Detection in Contaminated Water by Ga–N Nanomaterials Towards a Sustainable Future - (:unkn) unknown (AMG Transcend Association, 2025)
The aim of this research is to remove metal/loid ions of Na+, K+, Sn2+, Pb2+, Al3+, and As3+ from water due to nanomaterial-based gallium nitride nanocage (Ga–N). The electromagnetic and thermodynamic attributes of metal/loid cations trapped Ga–N were depicted by materials modeling. The encapsulation of metal/loid cations occurs via chemisorption. It has been studied the behavior of trapping of main group cations of Na+, K+, Sn2+, Pb2+, Al3+, As3+ by GaN–nc for sensing the water metal cations. Ga–N was modeled in the presence of metal/loid cations (Na+, K+, Sn2+, Pb2+, Al3+, As3+). Sample characterization was performed using CAM–B3LYP/EPR–3, LANL2DZ level of theory. The electric potential parameters extracted from NQR analysis have illustrated that the uptake of free potassium and sodium ions has been known to be associated with Ga–N, indicating that the K+ and Na+ ions encapsulated in this kind of nanocage can be internalized through a different pathway from other metal cations. Furthermore, the nuclear magnetic resonance (NMR) analysis indicated the notable peaks surrounding metal elements of Na+, K+, Sn2+, Pb2+, Al3+, and As3+ through the trapping in the Ga–N during ion detection and removal from water; however, it can be seen some fluctuations in the chemical shielding treatment of isotropic and anisotropy tensors. Based on the results of this research, the selectivity of metal ion adsorption by Ga–N (ion sensor) has been approved as K+> Na+> ˃ ˃ As3+ > Sn2+ ≈ Pb2+ > Al3+. Finally, it has been shown that for a given number of nitrogen donor sites in Ga–N, the stabilities of monovalent (M+), divalent (M2+) and trivalent (M3+) cation complexes are K+ΞGa–N > Na+ΞGa–N >˃˃ As3+ΞGa–N > Sn2+ΞGa–N ≈ Pb2+ΞGa–N > Al3+ΞGa–N. In this article, it is proposed that metal/loid cations–adsorbed can be used to decorate and enlarge the optoelectronic properties of Ga–N, which can be used to produce photoelectric devices for water treatment.